Accuracy of the urine point-of-care circulating cathodic antigen assay for diagnosing Schistosomiasis mansoni infection in Brazil: A multicenter study - Otavio Sarmento Pieri; Fernando Schemelzer Moraes Bezerra; Paulo Marcos Zech Coelho; Martin Johannes Enk; Tereza Cristina Favre; Carlos Graeff-Teixeira; Ricardo Riccio Oliveira; Mitermayer Galvão dos Reis; Lee Senhorinha de Almeida Andrade; Lilian Christina Nóbrega Holsbach Beck; Vivian Favero; Thainá Rodrigues de Souza Fialho; et al. (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: The World Health Organization recommends a market-ready, urine-based point-of-care diagnostic test for circulating cathodic antigens (CCA) to determine the prevalence of S. mansoni. This study evaluated the performance of the URINE CCA (SCHISTO) ECO TESTE® (POC-ECO), which is currently available in Brazil. Methods: Residents from eight sites with different prevalence estimates provided one urine sample for POC-ECO and one stool sample for Kato-Katz (KK) and Helmintex® (HTX) testing as an egg-detecting reference for infection status. Results: None of the study sites had significantly higher POC-ECO accuracy than KK. Conclusions: POC-ECO is not currently recommended in Brazilian schistosomiasis elimination programs.